2016
DOI: 10.1016/j.sjdr.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of third molar impaction in Libyan population: A retrospective radiographic study

Abstract: Objectives: The aim of the present study was to radiographically evaluate the pattern of third molar impaction in a sample of Libyan patients, in terms of age, gender, angulation of impaction, level of eruption and available retromolar space using panoramic radiographs. Furthermore, cross tabulation between patterns of impaction and gendernarch were evaluated for any significant difference. Study design: This retrospective study comprised 300 orthopantomograms (OPGs) of patients attending a private dental clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
26
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 22 publications
10
26
6
1
Order By: Relevance
“…This may explain why more females compared to males presented at earlier ages.Mesioangular impaction was reported as the most common impaction in males [4,17] while the most common impaction reported in females was distoangular impaction [2,4]. This is contrary to the findings of this study where a higher percentage of females presented with mesioangular impaction compared to males.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…This may explain why more females compared to males presented at earlier ages.Mesioangular impaction was reported as the most common impaction in males [4,17] while the most common impaction reported in females was distoangular impaction [2,4]. This is contrary to the findings of this study where a higher percentage of females presented with mesioangular impaction compared to males.…”
Section: Discussioncontrasting
confidence: 78%
“…Previous studies [2,4] reported no statistically significant difference between gender and mandibular third molar impaction while another study [9] reported significant association between gender and number of impacted teeth as well as the presence of impacted mandibular teeth.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Besides, there were significantly more mesioangular impactions in the mandible (78.5%) and more distoangular (66.9%) and vertical (56.4%) impactions in the maxilla. 9 Mesioangular impactions are probably the most common type and this may be due to their late development and maturation, path of eruption and lack of space in mandible at later age. 1 A study result from Sidlauskas 10 indicated that general lower dental arch crowding is an essential feature of the completed permanent dentition with 90% cases of space lacking.…”
Section: Introductionmentioning
confidence: 99%